Hubungan Self Management Dengan Kualitas Hidup Penderita Diabetes Melitus Tipe II Di RS PMI Kota Bogor Pada Tahun 2023 - Novi Haris Susilowati; Risky Kusuma H; Susaldi Susaldi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
The uncontrolled condition of DM patients can cause functional decline in the body which affects the quality of life and causes worsening of the condition. One of the actions to improve the quality of life is self-management. The purpose of this study was to determine the relationship between self-management and quality of life of type II diabetes mellitus patients. This type of research is quantitative with a cross sectional approach. It was found that the number of respondents was 98 people taken using purposive sampling. Research instruments to measure self-management using the diabetes self management questionnaire (DSMQ), and instruments to measure quality of life using WHOQOL-BREEF's quality of life. Data analysis using chi square and obtained the largest ODS Ratio with a number (2.314) with a P value of 0.070 where there is a relationship between physical activity and quality of life and it can be concluded that there is a relationship between self-management and the quality of life of diabetes mellitus patients with a positive association direction.